Multimediju izmantojums Latvijas ziņu portālos: satura un auditorijas analīze (2015. gada novembris - 2016. gada februāris) - Nazarova, Signe (Latvijas Universitāte, 2016)
Bakalaura darba “Multimediju izmantojums Latvijas ziņu portālos: satura un auditorijas analīze (2015. gada novembris – 2016. gada februāris)” mērķis ir noskaidrot multimediju piedāvājumu Latvijas ziņu portālos un izprast auditorijas vēlmes no multimediālā satura izmantojuma. Teorētiskajā daļā aplūkota teorija par mediju konverģenci, multimediju saturu, multimediju formātiem, multimediāliem ziņojumiem, interneta žurnālistiku, mediju lietojuma un apmierinājuma teorijas, kā arī digitālās tehnoloģijas ietekmi attiecībā uz medijiem. Empīriskajā daļā veikta daļēji strukturēta intervija ar divām mediju žurnālistēm, veikta interneta aptauja. Paralēli tam veikta kvantitatīvā kontenanalīze četros Latvijas ziņu portālos – delfi.lv, apollo.tvnet.lv, tvnet.lv un kasjauns.lv, lai noskaidrotu multimediju formātu piedāvājumu Latvijas ziņu portālos.

This Bachelor’s thesis “Multimedia use in Latvian news sites: content and audience analysis (November 2015 – February 2016)” the purpose is to find multimedia offers in Latvian news sites and understand audience’s expectations from the use of multimedia content. The Bachelor contains theoretical issues concerning multimedia, media convergence, it’s effect on content, multimedia forms, multimedia storytelling, online journalism, audience’s media use and gratification theory and digital technology development effects on media. This Bachelor’s thesis “Multimedia use in Latvian news sites: content and audience analysis (November 2015 – February 2016)” the purpose is to find multimedia offers in Latvian news sites and understand audience’s expectations from the use of multimedia content. The Bachelor contains theoretical issues concerning multimedia, media convergence, it’s effect on content, multimedia forms, multimedia storytelling, online journalism, audience’s media use and gratification theory and digital technology development effects on media. The research is based on two semi-structured interviews with journalists and internet survey. In the same time of these two tasks, there was made a quantitative content analysis in four Latvian news sites – delfi.lv, apollo.tvnet.lv, tvnet.lv and kasjauns.lv to find out multimedia form offer in Latvian news sites.
Multimedia use in Latvian news sites: content and audience analysis (November 2015 – February 2016)
Keywords: Komunikācijas zinātne; multimediji; Latvijas ziņu portāli; konverģence; auditorija; kvantitatīvā kontentanalīze